KEEFEKTIFAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V SDIT AZ-ZAHRA DEMAK - Muhammad Jamalul Huda; Nur Khotibul Umam (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2018)
Student’s cognitive learning outcomes in Mathematics subjects in SDIT Az-Zahra that has not met the minimum mastery criteria. The purpose of this study is to test the effectiveness of the PBL model to improve students’ cognitive learning results. This quantitative research was in the form of a quasi-experimental design (quasi-experiment) with nonequivalent control group design types (classes are experimental and control). The research subject was 60 students of V graders in SDIT Az-Zahra, it was determined by using purposive sampling technique. Data was in the form of cognitive and psychomotor students' learning result of science process skills, it was collected through observation, test, and documentation. The result of this study are as follows: there are differences in cognitive learning results between groups of students who follow the PBL model and group of students who not follow the PBL model, the value (t-calculate = 3:54> t-table= 2.74).